2021
DOI: 10.1186/s13287-021-02324-7
|View full text |Cite
|
Sign up to set email alerts
|

Upregulating CXCR7 accelerates endothelial progenitor cell-mediated endothelial repair by activating Akt/Keap-1/Nrf2 signaling in diabetes mellitus

Abstract: Background Endothelial progenitor cell (EPC) dysfunction contributes to vascular disease in diabetes mellitus. However, the molecular mechanism underlying EPC dysfunction and its contribution to delayed reendothelialization in diabetes mellitus remain unclear. Our study aimed to illustrate the potential molecular mechanism underlying diabetic EPC dysfunction in vivo and in vitro. Furthermore, we assessed the effect of EPC transplantation on endothelial regeneration in diabetic rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Normal level and function of circulating EPCs have been considered to be an endogenous protective factor of vascular diseases [33]. Studies have shown that patients from T2DM endure a reduced number and ability of EPCs [22,34]. In this study, we not only demonstrated T2DM patients had a lower level of circulating EPCs, but also first discovered the number of EPCs was well-correlated with decreased capillary density and increased non-perfused areas in retina.…”
Section: Discussionmentioning
confidence: 50%
“…Normal level and function of circulating EPCs have been considered to be an endogenous protective factor of vascular diseases [33]. Studies have shown that patients from T2DM endure a reduced number and ability of EPCs [22,34]. In this study, we not only demonstrated T2DM patients had a lower level of circulating EPCs, but also first discovered the number of EPCs was well-correlated with decreased capillary density and increased non-perfused areas in retina.…”
Section: Discussionmentioning
confidence: 50%
“…Given that the causative mutation for over 50% of BOR cases is not yet known, we predict that the lateral line of zebrafish will remain a powerful model to validate genomic polymorphisms from GWAS studies of BOR patients, and generate novel cellular and molecular insights with translational potential. On this regards, our findings raise the possibility that augmenting residual CXCR7 activity may improve the outcome of Eya1 mutations in humans (Jiang et al, 2021; Hughes and Nibbs, 2018). It also encourages the development of tissue engineering approaches to control collective cell migration aimed at clinical applications (Manivannan et al, 2012).…”
Section: Discussionmentioning
confidence: 74%
“…Highly expressed CXCR7 activated MAPK/ERK signaling through ligand-independent but β-arr2-dependent mechanisms [ 32 ]. Recent studies uncovered a novel role of β-arrestins in guiding receptor-mediated extracellular signals from cell membrane and transmitting through the cytoplasm to the nucleus by a complicated signaling network [ 33 , 34 ]. In the present study, we revealed that CXCL12/CXCR7 biased signal transmitted predominantly through β-arr1 to facilitate YAP1 nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%